Simulation of bone microdeformation of bruxism in anterior dental implant (Revista Nacional de Odontología, 2020)
Introduction: The purpose of this research was to evaluate the bone microdeformation of bruxism with dental implants by means of the finite element analysis (FEA) method.Materials and methods: One (1) Tapered Screw-Vent® implant (ref. TSVB10 Zimmer Dental): 13mm long x 3.7mm diameter with a 3.5mm platform, a Zirconium abutment, a screw, resin cement as the cementing agent, a monolithic ceramic crown of an upper central incisor, cortical bone and cancellous bone, was modeled using Solid Works 2010 (SolidWorks Corp., Concord, MA, USA), and later it was processed and analyzed with ANSYS version 14. The von Mises stresses and bone microdeformation (microstrain) were evaluated, applying oblique forces with magnitudes of 200N and 800N. This analysis allowed for evaluating and comparing the microdeformation, both in cortical bone and in cancellous bone in two magnitudes 200N and 800N.Results: Each one of the elements of the modeled structure (crown, abutment, screw, implant, cortical and cancellous bone) when subjected to increased stress, presented particular von Mises and microstrain values with a linear behavior. By subjecting the modeled structure to forces of 200N and 800N, none of the components suffered permanent deformation, that is, the yield point was not exceeded.Conclusion: According to the mechanical behavior of the modeled structure in magnitudes of 800N, it is possible to use a dental implant in a maxillary central incisor, since the parafunctional forces generated by bruxism are not higher than those presented in the modeled structure; Consequently, they do not generate permanent bone deformations.
Keywords: bruxism; dental implants; finite element analysis